Significance of Omega-3 Fatty Acids in the Prophylaxis and Treatment after Spinal Cord Injury in Rodent Models - Piotr Wojdasiewicz; Łukasz A. Poniatowski; Paweł Turczyn; Justyna Frasuńska; Agnieszka Paradowska-Gorycka; Beata Tarnacka (Hindawi Limited, 2020)
Polyunsaturated fatty acids (ω-3 acids, PUFAs) are essential components of cell membranes in all mammals. A multifactorial beneficial influence of ω-3 fatty acids on the health of humans and other mammals has been observed for many years. Therefore, ω-3 fatty acids and their function in the prophylaxis and treatment of various pathologies have been subjected to numerous studies. Regarding the documented therapeutic influence of ω-3 fatty acids on the nervous and immune systems, the aim of this paper is to present the current state of knowledge and the critical assessment of the role of ω-3 fatty acids in the prophylaxis and treatment of spinal cord injury (SCI) in rodent models. The prophylactic properties (pre-SCI) include the stabilization of neuron cell membranes, the reduction of the expression of inflammatory cytokines (IL-1β, TNF-α, IL-6, and KC/GRO/CINC), the improvement of local blood flow, reduced eicosanoid production, activation of protective intracellular transcription pathways (dependent on RXR, PPAR-α, Akt, and CREB), and increased concentration of lipids, glycogen, and oligosaccharides by neurons. On the other hand, the therapeutic properties (post-SCI) include the increased production of endogenous antioxidants such as carnosine and homocarnosine, the maintenance of elevated GSH concentrations at the site of injury, reduced concentrations of oxidative stress marker (MDA), autophagy improvement (via increasing the expression of LC3-II), and p38 MAPK expression reduction in the superficial dorsal horns (limiting the sensation of neuropathic pain). Paradoxically, despite the well-documented protective activity of ω-3 acids in rodents with SCI, the research does not offer an answer to the principal question of the optimal dose and treatment duration. Therefore, it is worth emphasizing the role of multicenter rodent studies with the implementation of standards which initially may even be based on arbitrary criteria. Additionally, basing on available research data, the authors of this paper make a careful attempt at referring some of the conclusions to the human population.